The forms of things unknown : teaching poetry writing to teens and adults - Savren, Shelley (Rowman & Littlefield, 2016)
The Forms of Things Unknown: Teaching Poetry Writing to Teens and Adults draws from Shelley Savren's forty years of teaching poetry writing to a diverse array of students, from teens with mental health issues to seniors to adults with developmental disabilities. Designed for use in a classroom or community setting, this book features forty-one lesson plans and nineteen more poetry-writing workshop ideas and provides guidance and inspiration for teaching poetry writing to teens and adults.